Dorsal-Ventral Differences in Modulation of Synaptic Transmission in the Hippocampus - Trompoukis, George; Papatheodoropoulos, Costas (Frontiers in Synaptic Neuroscience, 2020)
Functional diversification along the longitudinal axis of the hippocampus is a rapidly growing concept. Modulation of synaptic transmission by neurotransmitter receptors may importantly contribute to specialization of local intrinsic network function along the hippocampus. In the present study, using transverse slices from the dorsal and the ventral hippocampus of adult rats and recordings of evoked field postsynaptic excitatory potentials (fEPSPs) from the CA1 stratum radiatum, we aimed to compare modulation of synaptic transmission between the dorsal and the ventral hippocampus. We found that transient heterosynaptic depression (tHSD, < 2 sec), a physiologically relevant phenomenon of regulation of excitatory synaptic transmission induced by paired stimulation of two independent inputs to stratum radiatum of CA1 field, has an increased magnitude and duration in the ventral hippocampus, presumably contributing to increased input segregation in this segment of the hippocampus. GABAB receptors, GABAA receptors, adenosine A1 receptors and L-type voltage-gated calcium channels appear to contribute differently to tHSD in the two hippocampal segments; GABABRs play a predominant role in the ventral hippocampus while both GABABRs and A1Rs play important roles in the dorsal hippocampus. Activation of GABAB receptors by an exogenous agonist, baclofen, robustly and reversibly modulated both the initial fast and the late slow components of excitatory synaptic transmission, expressed by the fEPSPslope and fEPSP decay time constant (fEPSPτ), respectively. Specifically, baclofen suppressed fEPSP slope more in the ventral than in the dorsal hippocampus and enhanced fEPSPτ more in the dorsal than in the ventral hippocampus. Also, baclofen enhanced paired-pulse facilitation in the two hippocampal segments similarly. Blockade of GABAB receptors did not affect basal paired-pulse facilitation in either hippocampal segment. We propose that the revealed dorsal-ventral differences in modulation of synaptic transmission may provide a means for specialization of information processing in the local neuronal circuits, thereby significantly contributing to diversifying neuronal network functioning along the dorsal-ventral axis of hippocampus.